European security in a post-Brexit world - Paladini, Stefania; Castellucci, Ignazio (Brexit studies series., 2019)
The European Union's security strongly relies on the member states' capabilities of working together, sharing information and cooperating on issues of common interest. Security against transnational threats and challenges is better and more easily protected within a cooperative framework. With Brexit affecting all dimensions of UK and EU public life, this book creates a comprehensive insight into the complex issues facing security in a series of post-Brexit scenarios. Topics discussed include: Legal frameworks Law Enforcement and EUROPOL Internal Security Intelligence Agencies Information Systems and Sharing The Irish Land Border. European Security in a Post-Brexit World is a useful read for any academic researcher, student or practitioner working in the areas of Security, Criminology and Brexit Studies.